Combination of irrigation solutions in root canal treatment: Kombinasi larutan irigasi dalam perawatan saluran akar gigi - Destira, Nisya; Nurdin, Denny (Makassar Dental Journal, 2024)
Irrigation is an important stage to support the success of root canal treatment. Some irrigation solutions commonly used in root canal treatment include NaOCl and EDTA. This article describes the use of a combination of 5.25% concentration NaOCl and 17% EDTA irrigation solution in root canal treatment of tooth 21. A 20-year-old female presented for treatment of a broken left upper front tooth. Clinical examination showed positive vitality and percussion tests while the palpation test was negative; there was a picture of thickening of the lamina dura and periodontal ligament on radiographic examination. The patient was diagnosed with asymptomatic irreversible pulpitis with symptomatic apical periodontitis. At the initial stage, cavitary access preparation, working length measurement, preparation using rotary instruments, irrigation with a combination of NaOCl and EDTA were performed, administration of medicament, and root canal filling was performed followed by composite resin restoration. It was concluded that the combination of NaOCl and EDTA irrigation solutions in the root canal treatment of tooth 21 showed good results.